(3eTcGI GdeYbhd GdebJHS ef fhQ Gdefbhds - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMi GdCRdi GdbOje , GdbGOQ GdMcje CeG HYO CjgG dCN GdUai CHYO Gddg Yfc GdTHgGJ Effi fXQJ ai bhd QShd Gddg Udi dGdg Ydjg hSde djdI CSQi Hi OfhJ ef QHi s
(3BNQgG (B:s
(3hgPG GdYed EfeG gh ebOeI ef Gddg ddYHO , hgh Mce GdjOjf hJjSjQ GdbHVJjf , jfJL Gddg dg UaI GdbQH efg HeG JbOe ef GdUaI GdebQHI TQYkG Ch YbdkG hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B13s
(3HgG fXGe GdJYbjHIs
(3ai TQM MOjK djdI CSQi Hi OfhJ ef QHi hHfGg Ydi aUhd ai GNJUGe GdedC GdCYdi hhVY GdjOjf Hjf GdcJajf hESHGZ GdhVhA EdNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs